Experimental Research for the Production of “Butter Cookies” with Red Rice Flour Substitution - Dedy Kurniawan; Sherren Lorenza; Jesslyn Frances; Timotius Agus Rachmat (Jurnal Ilmiah Pertanian dan Peternakan, 2025)
Purpose: This study aims to examine public acceptance of butter cookies made with a partial substitution of wheat flour using brown rice flour and to identify differences in sensory attributes, including texture, color, aroma, and taste, compared to conventional butter cookies. Methods: Method research employs a quantitative approach using hedonic tests and organoleptic tests. Data were collected through structured questionnaires distributed to the general public and expert panelists. The hedonic test was used to measure the level of consumer preference, while the organoleptic test evaluated sensory differences between conventional butter cookies and those substituted with brown rice flour. Result: The results of the hedonic test show that butter cookies made with brown rice flour are generally well-received by consumers, with a favorable preference level. Organoleptic testing reveals significant differences in some sensory attributes, while others show no significant variation compared to the conventional recipe. Conclusions: Butter cookies with brown rice flour substitution are acceptable to the public and have the potential to be developed as an alternative product. The substitution influences specific sensory characteristics, although not all attributes differ significantly from conventional butter cookies. Limitations: This study is limited by the number of panelists and the scope of sensory attributes analyzed. In addition, variations in substitution ratios and long-term consumer acceptance were not explored. Contributions: This study contributes to the development of food product innovation by providing empirical evidence on the sensory acceptance of brown rice flour as a partial substitute for wheat flour in butter cookies.